2015
DOI: 10.1016/j.jog.2015.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Applying local Green's functions to study the influence of the crustal structure on hydrological loading displacements

Abstract: The influence of the elastic Earth properties on seasonal or shorter periodic surface mass loads due to atmospheric surface pressure and terrestrial water storage variations is usually modeled by applying a local isostatic model like a homogeneous half-space model, or by a one dimensional spherical Earth model like PREM from which a unique set of elastic load Love numbers, or alternatively, elastic Green's functions are derived. The drawbacks of these strategies are that, in the first case, the response accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 25 publications
1
57
1
Order By: Relevance
“…Even small perturbations to upper crustal layers, however, can yield large variations in the LGFs at short observer‐to‐load angular distances [cf. Wang et al , ; Dill et al , ; Bos et al , ], as exemplified by the high‐degree LLNs shown in Figure , the LGF differences between 1066A and PREM, and the LGF differences between the region‐specific (CR and SNA) and globally averaged Earth models (PREM, STW105, and AK135f).…”
Section: Resultsmentioning
confidence: 99%
“…Even small perturbations to upper crustal layers, however, can yield large variations in the LGFs at short observer‐to‐load angular distances [cf. Wang et al , ; Dill et al , ; Bos et al , ], as exemplified by the high‐degree LLNs shown in Figure , the LGF differences between 1066A and PREM, and the LGF differences between the region‐specific (CR and SNA) and globally averaged Earth models (PREM, STW105, and AK135f).…”
Section: Resultsmentioning
confidence: 99%
“…The La Niña subsidence is consistent between GPS measurements and GRACE predictions in spatial pattern (Figure f). The GRACE magnitude is found to be generally smaller than GPS, possibly indicating inefficacy of the 1‐D elastic Earth model used to compute the deformation [ Dill et al ., ]. The calculated trend after the La Niña from GRACE confirms the GPS observations in most places (Figure g).…”
Section: Interannual Change Before During and After The 2010–2011 Lmentioning
confidence: 99%
“…However, according to Dill et al . [], such effects cause a maximum of 10% in the annual vertical displacements over western Greenland.…”
Section: Discussionmentioning
confidence: 70%
“…We note that the analysis described above does not quantify the effects of lateral variations of crustal structure on the modeled loading displacements. However, according to Dill et al [2015], such effects cause a maximum of 10% in the annual vertical displacements over western Greenland.…”
Section: Performance Of Modeled Surface Mass-loading Displacementsmentioning
confidence: 99%